2020
DOI: 10.1038/s41598-020-65980-4
|View full text |Cite
|
Sign up to set email alerts
|

Wideband Magnetic Excitation System for Atomic Force Microscopy Cantilevers with Megahertz-Order Resonance Frequency

Abstract: Small cantilevers with a megahertz-order resonance frequency provide excellent sensitivity and speed in liquid-environment atomic force microscopy (AFM). However, stable and accurate oscillation control of a small cantilever requires the photothermal excitation, which has hindered their applications to the studies on photo-sensitive materials. Here, we develop a magnetic excitation system with a bandwidth wider than 4 MHz, enabling a light-free excitation of small cantilevers. In the system, a cantilever with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…This direct excitation of the cantilever successfully eliminates the spurious resonances in the liquid [31] with a Q-factor of 3-20. [48,49,[55][56][57] However, there still exist several shortcomings in magnetic excitation. First, the existence of magnetic coatings or magnetic particles increases the complexity of cantilever fabrication.…”
Section: Excitation Methodsmentioning
confidence: 99%
“…This direct excitation of the cantilever successfully eliminates the spurious resonances in the liquid [31] with a Q-factor of 3-20. [48,49,[55][56][57] However, there still exist several shortcomings in magnetic excitation. First, the existence of magnetic coatings or magnetic particles increases the complexity of cantilever fabrication.…”
Section: Excitation Methodsmentioning
confidence: 99%
“…It has already been demonstrated that overly sensitive dynamic responses to external forces such as tip-sample interaction forces are simply acquired by exploiting multifrequency excitation schemes [2][3][4][5][6]. The micro-cantilever can be excited using different methods such as photoacoustic [7], magnetic [8], electrostatic [9], and piezoelectric [10] methods. When compared to monomodal operations, implementing multi-frequency excitation schemes for driving an Atomic Force Microscopy (AFM) micro-cantilever can yield higher observables sensitivity to tip-sample interaction force at the fundamental (first) or the higher eigenmodes [11,12].…”
Section: Introductionmentioning
confidence: 99%